Keteladanan Guru Madrasah Aliyah Di Aceh - Nurma Dewi (Kalam: Jurnal Agama dan Sosial Humaniora, 2022)
The role of a teacher in school is not only to teach, but also to educate. A teacher is required to provide positive role modelling to students when educating them. In the last decade, however, most teachers did not show any proper role modelling. Motivated by such a finding, the study sought to investigate this issue.